Sustainable Tourism Goals Indicator: Challenges and Gap Analysis for Achieving Low Carbon Tourism in Chiang Mai - Kanokwan Khiaolek; Korawan Sangkakorn; Walinpich Kumpiw; Det Damrongsak; Wasan Puttiput; Tassawan Jaitiang; Varoon Raksakulkarn (Chemical Engineering Transactions)
Thailand adopted the Sustainable Tourism Goals (STGs) schemes in late 2023 which comprise 17 dimensions applied from UN-SDGs with a total of 86 indicators. The aim is to support sustainable development in the two major tourism sectors: hotel and transport. This paper emphasizes on the context of STG 7 (Clean energy) and 13 (Climate action) in tourism sector in Chiang Mai which is major tourist destination province in Northern Thailand. By using the onsite survey to 10 hotels and 10 transport companies, it was found that there were four major barriers to accelerate the low carbon target; i.e. (i) financial barriers, (ii) policy and institutional barriers, (iii) technology and innovation barriers, and (iv) knowledge barriers. Policy recommendations have been discussed. For the GHG mitigation potential after scaling up to the provincial level, there are vast mitigation potential of around 15,192.17 tCO2-eq/y. Transitioning to using alternative energy sources from solar cells can reduce GHGs by 14,243.86 tCO2-eq/y. Converting vehicles from diesel fuel to electric power can also reduce GHGs by 948.31 tCO2-eq/y. More incentives for entrepreneurs, such as promoting energy conservation, using renewable energy, and fostering innovation should be strongly considered to achieve the STGs. Full supports on climate change issues from top-level management play an important role to the success of low carbon pathway for tourism businesses.